Fragmentation and hazard analysis of brittle materials under far-field blast loading. Issue 7 (May 2022) - Hatfield, John E; Davidson, James S
When subjected to blast loading, brittle building components such as glass and masonry tend to break into fragments that are propelled at hazardous high velocities. There has been copious research on defining the design resistance of structures subjected to extreme dynamic loading, but research that relates the loading characteristics to fragmentation velocity and lethality is lacking in some areas. A review of research concerning fragmentation of brittle materials in dynamic loading scenarios, concentrating on far-field blast loading, was conducted. Fragmentation principles and their application in, analytical, statistical, numerical, and other varied modeling approaches were examined. Special attention was given to research evaluating fragment generation and velocity calculation above the level required for design of structural members and suitable for occupant hazard calculation. By surveying fragmentation research key factors that affect fragmentation behavior, velocity, and hazard across modeling efforts are developed and discussed.